Interior design illustrated - Ching, Francis D. K. 1943-; Binggeli, Corky (Wiley, 2018)
Interior Design Illustrated is the definitive guide to design for interior spaces. Richly illustrated in author Francis Ching’s signature style, this book introduces complex design concepts in a visually stunning format; from defining the space and using the elements of design, to planning building systems and incorporating sustainable materials, this volume embodies the idea that beauty and function are not separate entities, but two parts of a whole. This new fourth edition has been updated to reflect the latest building codes and design practices, with discussion of new materials related to acoustics, lighting, and sustainable furnishings. Renewed attention to sustainability includes new information on energy conservation, design for longevity and adaptive reuse of existing buildings, as well as an updated discussion on LED lighting, workplace design, use of color, and computer modeling software to provide a well-rounded view of how interior design firms are working today. --Provided by publisher.